Borders of a lip : Romanticism, language, history, politics - Plug, Jan (State University of New York Press, 2003)
Explores the role of language, history, and politics in Romantic literature and thought, from Kant to Yeats.
Keywords: Romanticism -- Europe.; European literature -- 19th century -- History and criticism.; Romantisme -- Europe.; Littérature européenne -- 19e siècle -- Histoire et critique.; TRAVEL -- Special Interest -- Literary.; LITERARY CRITICISM -- General.; European literature; Romanticism; Europe; 1800-1899; Criticism, interpretation, etc.